Applied social research : a tool for the human services - 229567 Monette, Duane R.; Sullivan, Thomas J. 1944-; DeJong, Cornell R. (Australia ; Belmont, CA : Brookscole, 2011)
Includes bibliographical references (p. 509-531) and indexes